Contextual learning: education through inter-cultural dialogue of elite and indigenous-indigent - Ibhakewanlan, John-Okoria (2015)
Universal access to education has been an urgent concern since the establishment of the United Nations’ Millennium Development Goals or MDG. While aiming at ‘Education for All’, the MDG did not specify what kind of education nor how that education would be delivered. Besides the emphasis on access, apparent in the various attempts to ensure provision of education for the world’s poor, there has been also focus on material resources -especially a reliance on foreign aid. This author argues that what is needed in the long-term is a localized or Culturally Responsive approach that includes a consideration of the question of justice–particularly the issue of socio-economic inequality.